Gas sensitive al membarane on n-type gan schottky diode / A. Y Hudeish, A. Abdul Aziz and Z. Hassan - Hudeish, A. Y.; Abdul Aziz, A.; Hassan, Z. (2004)
In this work, we have studied and fabricated a new, simple and small-size N2 and H2 sensitive Aluminum (AI) membrane/semiconductor (Al/n-GaN) Schottky diode sensor. Experimental results revealed that, during the hydride or nitride formation process, the time response increased and enhanced with temperatures operation and the forward- currents is increased by the increase of temperature for air, nitrogen and hydrogen. It also demonstrates that the Schottky barrier height is indeed increased with increasing the temperatures for gases. Therefore, the studied device can be used in fabricating a high-performance hydrogen and nitrogen sensitive sensor.